Clinical and transcriptomic features of persistent exacerbation‐prone severe asthma in U‐BIOPRED cohort. Issue 4 (26th April 2022) - Hoda, Uruj; Pavlidis, Stelios; Bansal, Aruna T.; Takahashi, Kentaro; Hu, Sile; Ng Kee Kwong, Francois; Rossios, Christos; Sun, Kai; Bhavsar, Pankaj; Loza, Matthew; Baribaud, Frederic; Chanez, Pascal; et al.
Abstract: Background: Exacerbation‐prone asthma is a feature of severe disease. However, the basis for its persistency remains unclear. Objectives: To determine the clinical and transcriptomic features of frequent exacerbators (FEs) and persistent FEs (PFEs) in the U‐BIOPRED cohort. Methods: We compared features of FE (≥2 exacerbations in past year) to infrequent exacerbators (IE, <2 exacerbations) and of PFE with repeat ≥2 exacerbations during the following year to persistent IE (PIE). Transcriptomic data in blood, bronchial and nasal epithelial brushings, bronchial biopsies and sputum cells were analysed by gene set variation analysis for 103 gene signatures. Results: Of 317 patients, 62.4% had FE, of whom 63.6% had PFE, while 37.6% had IE, of whom 61.3% had PIE. Using multivariate analysis, FE was associated with short‐acting beta‐agonist use, sinusitis and daily oral corticosteroid use, while PFE was associated with eczema, short‐acting beta‐agonist use and asthma control index. CEA cell adhesion molecule 5 ( CEACAM5) was the only differentially expressed transcript in bronchial biopsies between PE and IE. There were no differentially expressed genes in the other four compartments. There were higher expression scores for type 2, T‐helper type‐17 and type 1 pathway signatures together with those associated with viral infections in bronchial biopsies from FE compared to IE, while there were higher expression scores of type 2, type 1 and steroid insensitivity pathway signatures in bronchial biopsies of PFE compared to PIE. Conclusion: The FE group and its PFE subgroup are associated with poor asthma control while expressing higher type 1 and type 2 activation pathways compared to IE and PIE, respectively. Abstract : In severe asthma, frequent exacerbator (FE) and persistent frequent exacerbator (PFE) are associated with poorer asthma control compared to infrequent exacerbator (IE) and persistent IE, respectively. CEACAM5 was the differentially‐expressed transcript in bronchial biopsies in FE compared to IE. In FE and persistent FE, there was an increase in the expression of type 1 and type 2 inflammatory pathways.